Adsorptive removal of emerging pollutants from groundwater by using modified titanate nanotubes. Issue 4 (August 2018) - Orona-Návar, Carolina; García-Morales, Raul; Rubio-Govea, Rodrigo; Mahlknecht, Jürgen; Hernandez-Aranda, Raul I.; Ramírez, Juan Gabriel; Nigam, K.D.P.; Ornelas-Soto, Nancy
Abstract: The increasing presence of chemicals and pharmaceuticals in rivers, lakes, and groundwater among others, represents a latent threat both to ecosystems and to human health. Conventional treatment methods for water hardly eliminate these pollutants, which are usually dissolved in low concentrations (μgL −1 or ngL −1 ). Therefore, the use of nanomaterials represents a viable alternative to eliminate them. Titanate nanotubes have been successfully used in adsorption of organic dyes as well as heavy metals, however, their use as an adsorbent of pharmaceuticals and other organic pollutants has been scarcely studied. In this work, unmodified titanate nanotubes as well as modified titanate nanotubes by using a surfactant, were synthesized and characterized to study the adsorption of six organic pollutants of interest through first and second order kinetic models, as well as, adsorption isotherms of Freundlich and Langmuir. The synthesized nanotubes showed good efficiency for the adsorption of persistent organic compounds, reaching a maximum adsorption percentage of 83%, 78%, 54%, 43%, 30% and 47% for 2, 4, 6-trichlorophenol, oxytetracycline, 2, 4-dichlorophenol, tolazamide, captopril, and metformin respectively. Moreover, removal of pollutants was also successfully carried out in groundwater samples.